الدور الريادي لصحافة جمعية العلماء المسلمين في نشر الوعي الوطني في المجتمع الجزائري - يحياوي, ليلى (جامعة الوادي - University of Eloued, 2018)
لم تكن صحافة جمعية العلماء المسلمين الجزائريين هي أوّل صحافة عربية عرفها الجزائريون لكنها كانت الصحافة الرائدة التي تركت بصمتها في ضمير ووجدان الفرد الجزائري، فهي الصحف التي أعادت للعربية مكانتها بين الجزائريين، وأعادت ربطهم بتراثهم ، ونسعى في هذه الدراسة إلى إبراز الدور الأهم لصحافة الجمعية في توعية الشعب وتحفيزه للدفاع عن حقوقه .The press of the Association of Algerian Muslim Scholars was not the first Arab press known to the Algerians, but it was the leading press that left its mark on the conscience and conscience of the Algerian individual. These newspapers restored the position of the Algerians among the Algerians and re-linked them to their heritage. Raising awareness and motivating the people to defend their rights.
The leading role of the press the Association of Muslim Scholars in spreading national awareness in Algerian society
مقال
Keywords: الدور، صحافة جمعية العلماء المسلمين ،الوعي الوطني ،الوعي الوطني ،المجتمع الجزائري; The role, the press of the Association of Muslim Scholars, the national awareness, the national awareness, the Algerian society